Ethnomathematical Exploration of Geometric Concepts in Betawi Traditional Food - Syifa, Mahda; Maharbid, Dian Anggraeni (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
This study aims to explore the ethnomathematical values contained in eight traditional Betawi foods, namely egg crust, goyang flowers, rangi cakes, ulite cakes, pepe cakes, dongkal cakes, ketapang seeds, and geplak cakes, and relate them to mathematics learning at the elementary school level, especially in flat building materials. Using a descriptive qualitative approach through observation and documentation, this study identifies various geometric shapes found in these foods. The results of the analysis show that flat shapes such as circles, squares, rectangles, triangles, and parallelograms are explicitly reflected in the visuals of traditional Betawi food. For example, the egg crust, shake kembang, and geplak cake show circular shapes; pepe cake and knuckle cake show square and rectangular shapes; dongkal cake is triangular; and ketapang seeds resemble the shape of a parallelogram. These findings indicate that traditional Betawi foods can be used as contextual learning media based on local culture to help students understand geometric concepts in a concrete way. In addition to the form aspect, mathematical value is also found in the measurement element, which adds to the potential for the integration of ethnomathematics in the elementary school curriculum. The visual shape of food that tends to remain unchanged confirms its existence as a traditional heritage, where shape change is considered a creation, not part of a tradition.